Selection of Apis mellifera by behavior and honey production in agroecosystems of Tabasco, Mexico - Payro-de la Cruz, Emeterio; Argüello-Nájera, Omar; May-Esquivel, Fernando; Catzim-Rojas, Francisco Javier; Gómez-Leyva, Juan Florencio (Ecosistemas y Recursos Agropecuarios, 2023)
Mexico occupies 10 th place in honey exports, Tabasco is lagging behind in 25 th place as a producer, national beekeeping is carried out mainly with Africanized bees whose highly defensive behavior and varroosis are the main factors that slow down its development. The objective was to select parent bees in different agroecosystems of the state for their honey production, docility and resistance to diseases. 165 commercial colonies located in Comalcalco, Cárdenas and Paraíso Tabasco were evaluated. A selection index was established (IS = 10 points): Honey production (HP = 5), docility (D = 2), hygienic behavior (HB = 1.5), rooming (G =0.5), varroa infestation in adult bees (VIAA = 0.5) and varroa infestation in capped brood (VICO = 0.5). Significant differences were found between the apiaries in four of the six variables evaluated and high variation in the colonies within the same apiary. 19 colonies with the  highest indices were selected, which showed low levels of VIAA and VICO, high HB (95%) and AC (28%), docility 4 and high HP = 45 kg Colony−1.. A low correlation was found between D and HP (r=0.292, p=0.000), .No correlation was found between HP and the rest of the variables. Due to the above, the importance of selecting the best parental bees is highlighted, using an IS, weighing the expression of genetic characteristics, ensuring continuity of the process over time.